Estimates of Total Factor Productivity in the Philippines - Caesar B. Cororaton; Janet S. Cuenca (Philippine Institute for Development Studies (PIDS), 2001)
The paper presents an updated TFP estimates in the Philippines. The present estimates were derived using a modified set of methodologies, thus may not be comparable with those derived in the previous estimates (Cororaton and Caparas 1999). Modifications were introduced in the method for computing sectoral employment, sectoral investment and sectoral capital stock. Based on the revised TFP estimates, one can observe favorable as well as unfavorable trends. Sectoral estimates showed improving TFP in the 1990s, although a number of the sectoral TFP levels are still negative. However, for the economy as a whole, 1990 saw a slight decline in TFP. This could indicate that there may seem to be some unfavorable resource allocation effects. Looking at the factor intensity results, the growth during the period could generally be described as capital accumulation type of growth. This is particularly true for nontradable sectors, specially the service-related sectors. The labor-capital ratios and the sources of growth analysis indicate a movement of capital towards these sectors, relative to the rest of the sectors. One factor which may have contributed to this type of resource movement is the prolonged real appreciation of the currency in face of an aggressive trade reform programs in the first half of the 1990s. This kind of an economic environment may not be conducive to production activities, both for domestic consumption and exports. In a period when capital inflow is massive, which actually transpired during the first half of the 1990s, nontradable, service sectors could become an attractive destination of capital.
Keywords: 330; productivity; total factor productivity; Produktivität; Schätzung; Philippinen